The Shift of the Intestinal Microbiome in the Innate Immunity-Deficient Mutant rde-1 Strain of C. elegans upon Orsay Virus Infection - Guo, Yuanyuan; Xun, Zhe; Coffman, Stephanie R.; Chen, Feng (Frontiers in Microbiology, 2017)
The status of intestinal microbiota is a determinant of host health. However, the alteration of the gut microbiota caused by the innate immune response to virus infection is unclear. Caenorhabditis elegans and its natural virus Orsay provide an excellent model of host–virus interactions. We evaluated the intestinal microbial community complexity of the wild-type N2 and the innate immunity-deficient mutant rde-1 (ne219) strains of C. elegans upon Orsay virus infection. The gut microbiota diversity was decreased in rde-1 (ne219) mutant animals, and a large number of genes were associated with the difference between infected and uninfected rde-1 (ne219) mutant animals. Therefore, this study provides the first evaluation of the alterations caused by Orsay virus on intestinal microbiota in wildtype and innate immunity-deficient animals using C. elegans as the model species. Our findings indicate that virus infection may alters the microbiome in animals with defective immune response.